Description of a new cyprinid species, Labeo meroensis n. sp. (Teleostei: Cyprinidae), from the River Nile - Moritz, Timo (Zootaxa, 2007)
Labeo meroensis, new species, is described from the River Nile between the 6th and 5th cataract at Shendi and Atbara, Republic of Sudan. It is a small species, up to 52.5 mm standard length, resembling some species of the Labeo parvus- group. It is distinguished from all other African Labeo species by the combination of the following characters: cylindriform body, transverse plicae on the inner surface of the lips, 5.5 scale rows between lateral line and mid dorsal line, 39 to 41 scales in lateral line, 16 scales around the caudal peduncle and eye-diameter more than 21% of head-length.